Toxicity of Four Plant Based Products Against Three Stored Product Pests - Talukder, Debashish; Khanam, LA Muslima (Journal of Bio-Science, 2011)
Context: Plant essential oil play an important role in stored product pests protection. Emulsified oil can easily mix with water and also revealed the same insecticidal activity as essential oil of plants that could be used in store as well as in the field as an alternative synthetic insecticide. Objectives: The objective of this study is to investigate the efficacy of emulsified petroleum ether extract of Acorus calamus L. rhizome alone and three other combination of plant materials against three stored product pests, viz. Callosobruchus chinensis L., Sitophilus oryzae (L.) and Tribolium castaneum (Herbst) in adult phase in laboratories condition. Materials and method: Petroleum ether extract of different plant parts were emulsified. The emulsified products were A. calamus rhizome alone, A. calamus + Corchorus capsularis L. seed, A. calamus + Thevetia neriifolia Juss. seed and A. calamus + Zingiber cassumunar Roxb. rhizome. The residual film technique method was conducted to determine the LC50 value of above mentioned plant extract against three stored product pests. Results: Noticeable mortality was noted for all species after 24 and 48 hours of the treatment with the emulsified products, although highest mortality of C. chinensis was observed with A. calamus alone after 24 hours but it varied at 48 hours where the A. calamus + T. neriifolia showed the most effective result. The LC50 values of A. calamus alone products were 13.30 and 6.59 µgcm-1 and for A. calamus + T. neriifolia were 18.37 and 4.45 µgcm-1 against C. chinensis adults after 24 and 48 hours treatment respectively. A. calamus + T. neriifolia products showed the lowest LC50 values (43.27 µgcm-1) against Sitophilus oryzae at 24 hours treatment but it varied at 48 hours where A. calamus (L.) alone (13.72 µgcm-1) was found to be the most effective toxicant. A. calamus alone showed the lowest LC50 values (166.78 and 123.55 µgcm-1) against T. castaneum adults after 24 and 48 hours treatment. Conclusion: Use of plants in controlling insect infestation would offer desirable solutions, especially in developing tropical countries, where plants are found in abundance everywhere, throughout the year. Key words: Plant extract; Contact toxicity; Callosobruchus chinensis; Sitophilus oryzae; Tribolium castaneum. DOI: 10.3329/jbs.v17i0.7124 J. bio-sci. 17: 149-153, 2009